RANCANG BANGUN PROTOTIPE SISTEM MONITORING ATS-AMF DAN BATTERY CHARGER MENGGUNAKAN TELEGRAM DI PERUMDA AIR MINUM TIRTA SANJIWANI UNIT PRODUKSI BLANGSINGA - Triandani Ayuningsih, Ni Nyoman; Indra Partha, Cokorde Gede; Arta Wijaya, I Wayan (Jurnal SPEKTRUM; Vol 11 No 1 (2024): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2024.v11.i01.p23, 2024)
The monitoring system of the Automatic Transfer Switch - Automatic Mains Failure (ATS-AMF) and battery charger is necessary to facilitate operators in remotely monitoring the system, thus ensuring the continuous supply of water to consumers. An Internet of Things (IoT)-based monitoring system does not require operators to always be on standby at the location, operators can monitor the system remotely outside their working hours. The prototype system is designed using the NodeMCU ESP32 DEVKIT V1 microcontroller and Telegram application for sending and receiving messages remotely, as well as providing spam notifications when disruptions occur in the ATS-AMF and battery charger systems. Data sent from the ATS-AMF includes voltage, frequency, current, power, the power source being used, and disruption data from both the PLN electricity source and the generator. Data sent from the battery charger includes voltage, current, battery charging stages, battery state of charge, and disruption data. Test results show a 100% success rate in data transmission through the Telegram chatbot, with an average delay ranging from 4.8 seconds to 5.7 seconds. This monitoring system ensures effective remote monitoring to maintain the smooth flow of electricity and the continuous supply of water to consumers.